The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1808-86942010000100019
|View full text |Cite
|
Sign up to set email alerts
|

Quedas em idosos com Vertigem Posicional Paroxística Benigna

Abstract: Summary Benign Paroxysmal Positional Vertigo (BPPV) can cause falls, especially in the elderly. Aim to study whether or not elderly patients with BPPV have a reduction on their falls after the particle repositioning maneuver (PRM). Materials and Methods retrospective study including elderly with BPPV who had fall(s) during the last year. All patients were submitted to the PRM according to the affected semicircular canal (SCC). After the aboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 43 publications
4
56
1
14
Order By: Relevance
“…Other studies showed the balance changes as a source of morbidity and mortality in people aged over 75 years, which fall could be the mainly complication, caused by intrinsic and extrinsic factors as the loss of autonomy and quality of life, what should become the object, not only for future research but priority care in the processes of primary and secondary intervention population 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed the balance changes as a source of morbidity and mortality in people aged over 75 years, which fall could be the mainly complication, caused by intrinsic and extrinsic factors as the loss of autonomy and quality of life, what should become the object, not only for future research but priority care in the processes of primary and secondary intervention population 5 .…”
Section: Discussionmentioning
confidence: 99%
“…However, 2010 data estimate that 30 % of people over age 65 relate a fall event at least once a year and it could be represent around 70 % of accidental deaths in people aged 75 years or more 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Of the ten listed papers, we found nine 18,19,[23][24][25][26][27][28][29][30] (Chart 1). As far as clinical evolution is concerned, 990 (77.9%) patients became asymptomatic or improved after the first treatment done by means of the repositioning maneuver.…”
Section: Resultsmentioning
confidence: 99%
“…Before treating the patient, the maneuver can be negative for BPPV in a first assessment and positive in another one, on the same day or in a different day. Many BPPV cases did not have positioning nystagmus or dizziness at the time of the maneuver, which does not rule out the diagnostic maneauver 18,19,27 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation